Antimicrobial activity of crude extracts obtained from Chaetocarpus castanocarpus Roxb Thw. against human pathogens (Chittagong University Journal of Biological Sciences, 2013)
An attempt was made to investigate the antibacterial and antifungal activities of Petroleum ether, carbon tetrachloride, chloroform and ethyl alcohol extracts from Chaetocarpus castanocarpus against ten human pathogenic bacteria viz., Shigella dysenteriae, Salmonella typhi, S. paratyphi, Bacillus subtilis, B. cereus, B. megaterium, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Vibrio cholerae and three human pathogenic fungi viz., Aspergillus niger, A. ochraceus, and A. ustus using disc diffusion and poisoned food method respectively. The chloroform and ethyl alcohol extracts showed good antibacterial and antifungal activity against the tested organisms. The crude extract of chloroform exhibited the largest zone of inhibition (26 mm in diameter with 2000 mg/disc extract) against S. dysenteriae. In case of fungi, the highest percentage of inhibition (42.5.0% with 100 mg/ml medium) was recorded against A. ustus. The MICs were determined by broth macrodilution method. The lowest MIC (750 mg/ml) was recorded against B. megaterium towards chloroform and ethanol extract, and V. cholerae towards chloroform extract. In case of fungi, chloroform and ethanol extract exhibited the lowest MIC (2000 mg/ml) against A. ustus, and chloroform extract against A. niger. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13389 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):83-90, 2009